1997
DOI: 10.1080/02841859709172413
|View full text |Cite
|
Sign up to set email alerts
|

Angiography in non-traumatic brain haematoma

Abstract: There are groups of patients with ICH in whom the CT features are highly suggestive of AVM or aneurysm rupture. If the initial angiography is negative in these cases, careful follow up by repeat angiography and/or MR imaging is essential. However, potentially treatable abnormalities cannot be excluded with certainty by the distribution of the haematoma on CT alone, even if there is a history of pre-existing hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 6 publications
(1 reference statement)
2
18
0
2
Order By: Relevance
“…We identified patients with clinical and radiologic characteristics that predict a higher yield of MDCTA for the presence of an underlying vascular etiology for the IPH (Table 5). Our results are similar to those of most prior conventional angiography studies, in which yields of 50%-89% in patients younger than 40 -50 years, 7-9,10,15 significant differences in the yield of conventional angiography for different IPH locations, [7][8][9][10][11][12][13][14][15] increased prevalence of aneurysms in women, 16 and lower angiographic yields in patients with hypertension and/or impaired coagulation are reported. 7,8,11,14,15 Given the relatively lower sensitivity of MDCTA for the detection of small vascular lesions, patients with these clinical and radiologic characteristics who have a negative initial CTA should undergo conventional angiography to exclude a small vascular lesion as the IPH etiology.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We identified patients with clinical and radiologic characteristics that predict a higher yield of MDCTA for the presence of an underlying vascular etiology for the IPH (Table 5). Our results are similar to those of most prior conventional angiography studies, in which yields of 50%-89% in patients younger than 40 -50 years, 7-9,10,15 significant differences in the yield of conventional angiography for different IPH locations, [7][8][9][10][11][12][13][14][15] increased prevalence of aneurysms in women, 16 and lower angiographic yields in patients with hypertension and/or impaired coagulation are reported. 7,8,11,14,15 Given the relatively lower sensitivity of MDCTA for the detection of small vascular lesions, patients with these clinical and radiologic characteristics who have a negative initial CTA should undergo conventional angiography to exclude a small vascular lesion as the IPH etiology.…”
Section: Discussionsupporting
confidence: 79%
“…7,8,10,11,14,15 This is likely due to the older mean age in our patient population (65 years), compared with 42-52 years in prior studies, 7,8,10,11,14,15 and the higher prevalence of hypertension and impaired coagulation in our patient population (59% and 33%, respectively), compared with 13%-60% for hypertension, and 7%-14% for impaired coagulation in prior studies. [7][8][9][10][11][12][13][14][15] These differences in patient demographics likely reflect the lower threshold for performing a CTA compared with a conventional angiogram due to the lower risk of MDCTA in older patients and the emerging role of MDCTA as an important screening examination in the evaluation of patients presenting to the emergency department with IPH.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…In a prospective study of 100 consecutive cases of nontraumatic SICH, the authors identified aneurysms or AVMs in 49% of cases. 43 When a temporal lobe hematoma extended into the sylvian fissure or when it was associated with SAH, structural abnormalities were identified in more than 90% of cases. Although the diagnostic yield was lower in hypertensive patients, angiography still identified an AVM or aneurysm in 25% of hypertensive patients.…”
Section: Cerebral Angiographymentioning
confidence: 99%
“…Twelve studies described the yield of a single investigation. 4,5,[12][13][14][15][16][17][18][19][20][21] Investigation yield was mostly concerned with IADSA, 4,5,12-14,17,18,21 but 1 study concentrated on CT angiography 20 and 3, on MRI. 15,16,19 Three nonrandomized studies described the yield of strategies of delaying IADSA 3,22 or of IADSA or CT/MRA for putaminal hemorrhage.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%